The Effectiveness of K-W-L-A (Know, Want, Learned, Affect) Strategy in Improving Students’ Reading Comprehension at Senior Islamic High School 4 Agam - Suci Wahyuni; Fitrawati Fitrawati (Journal of English Language Teaching, 2023)
This study aims to examine the effectiveness of the K-W-L-A strategy on students' reading comprehension at Man 4 Agam. It is a quasi-experimental study. A test was utilized as a tool by researchers to collect data. There were 30 questions, however 3 of them were found to be invalid following the validity and reliability tests. The researcher corrected the invalid questions so they could be used again. Eleventh-grade student social studies at MAN 4 Agam took part in this research. There are 40 students consisting of two classes. The control group is eleventh-grade social 1. This class consists of 20 students. The experimental group is eleventh grade social 2 which consists of 20 students. Paired sample t-test research results, the K-W-L-A strategy significantly improved the reading comprehension abilities of the students. With a significance value smaller than 0.05, namely 0.000. This shows that pupils' reading comprehension skills can be considerably improved by effectively implementing the K-W-L-A approach.